Effects of long-term training on neutrophil function in male university judoists. Issue 4 (4th April 2008) - Yamamoto, Y; Nakaji, S; Umeda, T; Matsuzaka, M; Takahashi, I; Tanabe, M; Danjo, K; Kojima, A; Oyama, T
Abstract : Objectives: To clarify the effects of high-intensity and high-frequency long-term/chronic training on neutrophil function and serum levels of myogenic enzymes in male university judoists. Methods: The subjects were 24 male judoists who had stopped judo training for 6 months and then restarted their training. The following parameters were examined before and after a 2 h unified exercise loading (UEL) at the beginning of the restarted quotidian training (pre-training) and at 2 months, 4 months and 6 months thereafter: myogenic enzymes, neutrophil and leucocyte counts, and neutrophil phagocytic activity (PA) and oxidative burst activity as a measure of reactive oxygen species (ROS) production capability. Results: Myogenic enzymes that were measured after UEL at all four points significantly increased except for creatine kinase at the 2-month point (p<0.01 in each) and neutrophil counts significantly increased after UEL at the pre-training, 2-month and 4-month points (p<0.01 in each), but these changes became smaller from the 2-month point. PA significantly decreased after UEL at the pre-training and 2-month points (p<0.01 in each), but no change was seen at the 4-month and 6-month points. On the other hand, no change in ROS production per cell after UEL was seen at the pre-training point, but it significantly increased after UEL at the 2-month, 4-month and 6-month points (p<0.01 in each). Conclusion: The changing rate of the levels of UEL-mediated myogenic enzymes, neutrophil mobilisation and neutrophil function was seen to decrease at the 2-month, 4-month and 6-month assessments, compared with the pre-training point: these may comprise at least some of the long-term training effects.